Poverty reduction strategies via public-private partnerships: the role of e-government solutions in supporting supplier diversity programmes - Jeeva, Ananda; Wood, Lincoln (Information Science Reference (an imprint of IGI Global), 2012)
Government procurement practices influence large volumes of spending in communities and further procurement can be influenced through legislative efforts. Through these mechanisms government bodies carry significant influence on the way in which procurement spend occurs and they have the ability to influence the direction that the procurement may take. Carefully constructed parameters in public-private partnerships (PPP) can shift the focus of procurement activities towards engaging with the local businesses and communities. This represents an approach for government bodies to increase supplier diversity so that, in alignment with UN Millennium goals of poverty reduction, local suppliers can be provided with business opportunities and methods to reduce poverty. A two-focus approach is adopted; first, government drivers and policies are examined in the context of social engagement. Second, the roles and challenges faced by small firms in the local communities are highlighted. This demonstrates the way in which e-government procurement systems play a pivotal role in supporting local sourcing initiatives.